Table of Content - - (Journal of Educational and Psychological Sciences, 2024)
Table of Content: 1. The Role of Training Courses in Improving the Professional Performance of Principals in Private Schools in Bethlehem Governorate from their point of view Researcher/ Grace Nasri Hazboun 2. Education on Virtue in Islamic Educational Thought and Contemporary Western Philosophies - A Comparative Study. Dr. HAILAH FAISAL H ALOQAYLI. 3. Psychological counseling skills among female counselors in the secondary stage in the locality of Khartoum Dr. Ghada El ameen Ahmed 4. Reflective Thinking and its Relationship to Decision-Making Among Teachers of Gifted Students in Makkah Al-Mukarramah Researcher / Mada Khaled Al-Lahyani 5. The Level of Mental Health among Omani Students with Learning Disabilities during Coronavirus Pandemic from their Parents’ Perspective Ms. Maryam H. Al-Hinai, Dr. Suhail M. Al-Zoubi, Dr. Zubaida S. Shebani 6. Optimism and pessimism mediate the association between parental coronavirus anxiety and depression among healthcare professionals Dr. Zainab Shalal Al-Anzi 7. Challenges faced by female graduate students working in the private sector Ms. Raya Abdullah Al-Hammad, Ms.Fatima Jaber Al-Shehri, Ms.Ohood Saud Al-Shammari, Prof. Dr. Awatif Ibrahim Al-Saqri